1982
DOI: 10.1038/bjc.1982.301
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the cytotoxicity of radiosensitizers by modest hyperthermia: the electron-affinity relationship

Abstract: Summary.-The cytotoxicity of 3 electron-affinic radiosensitizers has been studied in Chinese hamster V-79 cells as a function of pH and modest hyperthermia. When equitoxic concentrations were used and temperature was increased from 34 to 41°C metronidazole, the compound with the lowest electron affinity showed the greatest enhancement of hypoxic-cell toxicity, and nitrofurantoin, the compound with the highest electron affinity, the least. The results can be explained if the mechanisms of toxicity involves a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Siemann (1982) reported that the combination of CCNU and MISO exerted an antitumour effect on murine tumours, but this was not the case with CCNU and MTR. In contrast, Rajaratnam et al (1982) reported that in a hyperthermic treatment at 41°C, MISO exhibited a smaller degree of cytotoxicity than MTR, when both these drugs were given in equitoxic concentrations. As shown in Table I, MTR is clearly less effective than MISO in combination with MCC.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Siemann (1982) reported that the combination of CCNU and MISO exerted an antitumour effect on murine tumours, but this was not the case with CCNU and MTR. In contrast, Rajaratnam et al (1982) reported that in a hyperthermic treatment at 41°C, MISO exhibited a smaller degree of cytotoxicity than MTR, when both these drugs were given in equitoxic concentrations. As shown in Table I, MTR is clearly less effective than MISO in combination with MCC.…”
mentioning
confidence: 85%
“…Stone (1978) and Honess et al (1978) reported that in in vivo experiments with murine tumours, local hyperthermia combined with MISO resulted in a delay in tumour growth. Hall et al (1977) and Rajaratnam et al (1982) reported that malignant cells cultured at high temperature showed a marked decrease in growth rate in the presence of MISO or MTR. In the present study, the combination of hyperthermia and MTR did not enhance the antitumour activity, while hyperthermia combined with MISO and MMC resulted in a significant delay in tumour growth.…”
mentioning
confidence: 99%
“…Hyper thermia may increase cell target producing intermediates that contribute to the cytotoxcity of RP-170. Further more, it is conceivable that chemical activation ofRP-170 is increased by the addition of thermal energy and that cellular repair systems are inhibited [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…The use of radiation sensitizing agents, including mi sonidazole (MISO) [1], and chemotherapeutic agents [2] in conjunction with hyperthermia [3][4][5] has shown prom ise both experimentally and clinically. Such a combined modality is more effective for disseminated malignant disease such as leukemia than for solid tumors [6].…”
Section: Introductionmentioning
confidence: 99%